2017
DOI: 10.1002/cbdv.201600291
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Least Studied Australian Eucalypt Genera: Corymbia and Angophora for Phytochemicals with Anticancer Activity against Pancreatic Malignancies

Abstract: While the pharmacological and toxicological properties of eucalypts are well known in indigenous Australian medicinal practice, investigations of the bioactivity of eucalypt extracts against high mortality diseases such as pancreatic cancer in Western medicine have to date been limited, particularly amongst the genera Corymbia and Angophora. Four Angophora and Corymbia species were evaluated for their phytochemical profile and efficacy against both primary and secondary pancreatic cancer cell lines. The aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In terms of structural differences, polyphenols can be further divided into four categories: phenolic acids, astragalus, lignans, and flavonoids ( Table 1 ). A couple of studies have demonstrated the dominant biomass polyphenols that are found in common foods, including gallic catechins in green tea, resveratrol in grapes, capsaicin in chilis and peppers, curcumin in turmeric, genistein in soybean, and gingerol in ginger ( Bhuyan, 2018 ). Investigation of the biological outcomes of these particular edible goods allows for a better understanding of the structural details related to the functionalities of polyphenols.…”
Section: Biomass Polyphenolsmentioning
confidence: 99%
“…In terms of structural differences, polyphenols can be further divided into four categories: phenolic acids, astragalus, lignans, and flavonoids ( Table 1 ). A couple of studies have demonstrated the dominant biomass polyphenols that are found in common foods, including gallic catechins in green tea, resveratrol in grapes, capsaicin in chilis and peppers, curcumin in turmeric, genistein in soybean, and gingerol in ginger ( Bhuyan, 2018 ). Investigation of the biological outcomes of these particular edible goods allows for a better understanding of the structural details related to the functionalities of polyphenols.…”
Section: Biomass Polyphenolsmentioning
confidence: 99%
“…Caspase 3/7-mediated apoptosis and morphological changes of cells were also witnessed in MIA PaCa-2 cells [123]. In a subsequent study [124], the same group of investigators found that Angophora floribunda extract exerted a greater cell growth inhibition followed by A. hispida in MIA PC-2 cells.…”
Section: Eucalyptusmentioning
confidence: 88%
“…- Leaves and bark are used as antiseptics, expectorants, and treatments for influenza and colds, toothaches [28,29] and diarrhoea [29]; hot water extracts of the dried leaves are used to treat colds, influenzas, respiratory infections and sinus congestion [30][31][32][33][34][35]; water extracts are also used to treat, vomiting, nausea, indigestion, bloating, irritable bowel and abdominal pain [30]; leaves are used in India and Africa to treat obesity, ageing, cardiovascular illnesses, diabetes and respiratory problems [36,37]; in Nigeria, leaves are boiled and consumed for the treatment of typhoid fever, stomach aches and malaria [38]; Dharawal people use leaves to treat inflammation, wounds and fungal infections [39]. Kino is traditionally used to treat diarrhoea and bladder inflammation and is applied to cuts and abrasions [40,41].…”
Section: Ethnomedical Uses Of Corymbia Speciesmentioning
confidence: 99%